Hubungan Aktivitas Fisik dengan Kualitas Hidup Pasien Hemodialisis Reguler - Br Manurung, Shofi 'Ainun Azzahra; Nasution, Bayu Rusfandi; Rey, Imelda (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Hemodialysis (HD) is one of the renal replacement therapies commonly used in patients with end-stage renal disease. Patients undergoing hemodialysis typically exhibit lower levels of physical activity compared to inactive yet healthy individuals. A decline in physical function and muscular strength may impair the ability to perform daily activities, ultimately affecting patients’ quality of life (QoL). This study aimed to examine the relationship between physical activity and quality of life among hemodialysis patients at Rumah Sakit Khusus Ginjal Rasyida Medan. Methods. This was an analytical observational study with a cross-sectional design involving 50 respondents undergoing hemodialysis therapy at Rumah Sakit Khusus Ginjal Rasyida Medan between July and November 2022. Participants were selected based on predetermined inclusion and exclusion criteria. The association between variables was analyzed using the Chi-square test. Results. Among the respondents, 72.0% were categorized as having a good quality of life, while 28.0% had a poor quality of life. Regarding physical activity levels, 48.0% of patients had moderate activity, 26.0% had high activity, and 26.0% had low activity. Bivariate analysis revealed significant associations between quality of life and physical activity (p = 0.007), as well as between quality of life and comorbidities (p = 0.024). Multivariate analysis indicated that physical activity was a significant predictor of quality of life, with a prevalence ratio (PR) of 4.429 (95% CI: 1.383–14.191). Conclusion. There is a significant association between physical activity and quality of life among hemodialysis patients at Rumah Sakit Khusus Ginjal Rasyida Medan.